Integrated Central-Autonomic Multifractal Complexity in the Heart Rate Variability of Healthy Humans - Lin, Der Chyan B.; Sharif, Asif (Frontiers in Physiology, 2012)
In this study, we introduce a novel approach to examine the heart-brain interaction underlying the multifractality in the heart rate variability of healthy humans. Via the autonomic perturbation induced by the passive head-up-tilt (HUT), empirical supports for the central-autonomic fractal correlation (CAFC) are presented based on the fractal properties in simultaneously recorded electroencephalography (EEG) and heart beat interval data. In particular, we show the measure of CAFC varies according to the fractal complexity of HRV. The result implies the change towards more (less) complex HRV fractal complexity is associated with a stronger (weaker) CAFC and is tested significantly different from the surrogate data. Using the HRV and EEG physiological correlates in the frequency domain, we further show that CAFC is significantly linked to the EEG Beta band activities and the HRV spectral measures in the supine position. These findings suggest a potential arousal factor underlying the physiological processing of the central influence in the HRV scale-free dynamics.